Covid-19: economics and finance - Magalhães, Luiz Augusto Ferreira (2022)
In December 2019, dozens of pneumonia-like cases in China led to the identification of SARS-CoV-2 (COVID-19 or new coronavirus), with a large spreading rate potential by historical epidemiological standards. Beyond health and epidemiological damages, COVID-19 brought substantial economic and financial downturns. After the outbreak of the pandemics, most governments around the world opted for measures like horizontal social distancing, lockdown, quarantines. Considering these events, we first explore how banks reallocate credit across Brazilian municipalities due to the COVID-19 using a difference-in-differences (DiD) approach. To extract causality from our results, we explore the heterogeneous timing and strength in which COVID-19 affected Brazilian municipalities and the pre-determined credit portfolios of Brazilian banks across different municipalities. We find that local financial conditions—measured in terms of total outstanding credit—improve in inland municipalities highly exposed to COVID-19. The credit increase is more substantial in inland municipalities with highly concentrated local credit markets, particularly by large banks; with low financial development levels; and more efficient courts. The growth to less financially-developed inland municipalities may result from either their higher distance to Brazilian capitals or the potential room for credit expansion in these places. Banks may also prefer reallocating credit to inland municipalities with more efficient courts to maximize recovery rates, as judicial cases tend to resolve faster. Second, we examine the relationship between the COVID-19 pandemic and hedging efficiency in commodities futures markets. In particular, we first evaluate the informational content of commodity futures by investigating whether futures prices are accurate and unbiased predictors of future spot prices. Then, we identify key financial and real economy transmission channels associated with the pandemic. We use all contracts from all commodities traded at Brazilian futures markets from 2018 to 2020. We document market inefficiency and biasedness for all commodities, that COVID-19 negatively correlates with hedge efficiency, and that liquidity, economic activity, exports, and agriculture’s employment share are possible channels of transmission to hedge efficiency. Our findings highlight the importance of understanding how countries suffer from exogenous and unpredicted shocks.